Contextual Learning of Islamic Religious Education with a Social Learning Approach at Senior High Schools in East Jakarta - Syarifah Soraya; Abdul Hadi; Hadi Yasin; Nur Fauziah; Kartika Sharaswati (Yayasan Darusssalam Bengkulu, 2026)
This research is motivated by the low attitude scores of students in Islamic Religious Education learning in Senior High Schools in East Jakarta, especially in Senior High School Jakarta Islamic School 1 and Senior High School Jakarta Islamic School 2. Based on preliminary data, the attitude scores of students in both schools only reached 40%. This condition indicates that Islamic Religious Education learning has not been fully able to shape religious attitudes, discipline, responsibility, social awareness, and positive behavior of students in everyday life. Therefore, it is necessary to develop a learning model that is able to connect Islamic Religious Education materials with the real-life context of students. The purpose of this research is to develop contextual learning of Islamic Religious Education with a social learning approach to improve the attitude scores of students in Senior High School Jakarta Islamic School 1 located in Ciracas District and Senior High School Jakarta Islamic School 2 located in Cipayung District, East Jakarta. The research method used is Research and Development (R&D) with the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The results of this research will produce a valid, practical, and effective learning model in improving the attitude scores of students. Contextual learning in Islamic Religious Education using a social learning approach can be a relevant alternative learning strategy to strengthen student character development in schools.